Behavioral modeling of integrated phase-change photonic devices for neuromorphic computing applications - Santiago G.-C. Carrillo; Emanuele Gemo; Xuan Li; Nathan Youngblood; Andrew Katumba; Peter Bienstman; Wolfram Pernice; Harish Bhaskaran; C. David Wright (APL Materials, 2019)
The combination of phase-change materials and integrated photonics has led to the development of new forms of all-optical devices, including photonic memories, arithmetic and logic processors, and synaptic and neuronal mimics. Such devices can be readily fabricated into photonic integrated circuits, so potentially delivering large-scale all-optical arithmetic-logic units and neuromorphic processing chips. To facilitate in the design and optimization of such large-scale systems, and to aid in the understanding of device and system performance, fast yet accurate computer models are needed. Here, we describe the development of a behavioral modeling tool that meets such requirements, being capable of essentially instantaneous modeling of the write, erase, and readout performance of various integrated phase-change photonic devices, including those for synaptic and neuronal mimics.